Transplant‐associated thrombotic microangiopathy and immune haematological complications following intestine‐containing organ transplantation: experience from over 100 consecutive cases. (5th May 2021) - Thomas, Will; Foukaneli, Theodora; Cosgrove, Joyce; Massey, Dunecan; Woodward, Jeremy; Middleton, Stephen; Besser, Martin; Russell, Neil; Amin, Irum; Butler, Andrew; Sharkey, Lisa
Summary: Descriptions of passenger lymphocyte syndrome (PLS), immune cytopenias and transplant‐associated thrombotic microangiopathy (TA‐TMA) after intestine‐containing transplants remain scarce. We describe our centre's experience of these complications from 2007 to 2019. Ninety‐six patients received 103 transplants. PLS occurred in 9 (9%) patients (median 12 days post‐transplant); all due to ABO antibodies. There were 31 minor ABO mismatch transplants. No patient required change in immunosuppression. Immune cytopenias (excluding PLS) occurred in six patients at an incidence of 1·7/100 patient years; three immune haemolysis, one immune thrombocytopenia, one acquired Glanzmann's and one immune neutropenia; 50% occurred with other cytopenias. All cases eventually responded to treatment, with a median of four treatments (range 1–8) and 5/6 were treated with rituximab. One patient with immune haemolysis required bortezomib. Complications were common in patients with immune cytopenias; 4/6 with infection needing intravenous antibiotics and 3/6 with venous thromboembolism. In 3/6 cases, a secondary cause for the immune cytopenia was evident. Switching from tacrolimus to ciclosporin was not necessary. There were five cases of transplant‐associated thrombotic microangiopathy (TA‐TMA; 1·5/100 patient years) requiring calcineurin inhibitor withdrawal; two cases associated with acute rejection. Two cases were managed with plasma exchange, one with plasma infusions and one with eculizumab. Further research in this patient group is required.